2020
DOI: 10.3390/microorganisms8091257
|View full text |Cite
|
Sign up to set email alerts
|

Papaya Fruit Pulp and Resulting Lactic Fermented Pulp Exert Antiviral Activity against Zika Virus

Abstract: There are a several emerging and re-emerging RNA viruses that are prevalent around the world for which there are no licensed vaccines or antiviral drugs. Zika virus (ZIKV) is an example of an emerging virus that has become a significant concern worldwide because of its association with severe congenital malformations and neurological disorders in adults. Several polyphenol-rich extracts from plants were used as nutraceuticals which exhibit potent in vitro antiviral effects. Here, we demonstrated that the papay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…[18][19][20][21] In addition, papaya fruit pulp was recently reported to exert antiviral activity against Zika virus. 22 Papaya comprises a wide range of phytocompounds that may induce antiviral activities against different classes of viruses. 23 Fatty acids, sterols, and triterpenoid compounds represent the major compounds present in C. papaya.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] In addition, papaya fruit pulp was recently reported to exert antiviral activity against Zika virus. 22 Papaya comprises a wide range of phytocompounds that may induce antiviral activities against different classes of viruses. 23 Fatty acids, sterols, and triterpenoid compounds represent the major compounds present in C. papaya.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism of action has been described for various natural compounds such as EGCG, delphinidin, curcumin, geraniin and berberine against ZIKV and DENV [ 22 , 23 , 31 , 46 , 47 ]. Numerous studies have highlighted the capacity of medicinal plants extracts to neutralize ZIKV or DENV infectivity [ 19 , 21 , 22 , 23 , 24 , 25 , 30 , 31 , 48 , 49 ]. Here, using a panel of virological assays, we demonstrated that cranberry pomace extract, as well as EGCG, is capable of neutralizing the infectivity of the Asian epidemic strain of ZIKV in zebrafish at non-toxic doses.…”
Section: Discussionmentioning
confidence: 99%
“…The development of efficient natural therapeutics against DENV and ZIKV infection has become a priority because of the risk of CZS, especially in regions infested by mosquito vectors of disease [ 8 , 16 , 17 , 18 ]. It has been reported that plant extracts rich in flavonoids, terpenoids, coumarins, polyphenols and even some essential oils may inhibit DENV and ZIKV infection [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Previous studies showed that epigallocatechin gallate (EGCG), delphinidin, isoquercitrin, resveratrol, geraniin and curcumin inhibit ZIKV and DENV infection at different stages of the viral cycle [ 20 , 23 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, some plant species stand out based on their effectiveness at very low concentrations; these are Carica papaya (Caricaceae) ( Haddad et al, 2020 ), Cissampelos pareira (Menispermaceae) ( Ashraf et al, 2017 ), and B. rotunda (Zingiberaceae) ( Kanjanasirirat et al, 2020 ), and the findings suggest sufficient specificity (extracts were used at concentrations of less than 10 µg/mL) that these might be good candidates for developing antiviral agents and merit further evaluation against a broader group of viruses. Particularly, B. rotunda extract and its isolated component panduratin A have promising antiviral activity against SARS-CoV-2 (COVID-19) ( Kanjanasirirat et al, 2020 ).…”
Section: An Updated List Of Bioactivities Of the Selected Plantsmentioning
confidence: 99%